INOVASI PEMANFAATAN TANAMAN BAMBU MENJADI LAMPU HIAS - Sjahruddin, Herman; Djaya, Subhan; Linan Langodai, Theresia Megawati; Hasmia, Hasmia; Rosniati, Rosniati; Saniapon, Nining (LPPM Univ. Ibn Khaldun Bogor, 2022)
Utilization of bamboo plants as a form of innovation by increasing the utility of bamboo into lanterns. The abundance of bamboo resources is the reason for carrying out community service activities through training activities carried out for approximately one month in Sunggumanai Village, District. Pattallassang, Gowa Regency, South Sulawesi Province. The training is carried out as an effort to support the fulfillment of the economic needs of the community through the use of abundant natural resources in the village through the use of bamboo plants. The stages of the implementation of this activity began with observation activities and then continued with training on making bamboo lantern products. This product training activity was carried out at the Village Office in collaboration with village institutions (Bumdes) which was attended by village communities who in this activity acted as training participants. From the implementation of this activity, various benefits were obtained, namely an increase in people's income, changes in behavior, increased knowledge and skills, because the slowly made lanterns gain sympathy from consumers and in turn can increase people's income